2017
DOI: 10.1038/bjc.2017.129
|View full text |Cite
|
Sign up to set email alerts
|

GP participation in increasing uptake in a national bowel cancer screening programme: the PEARL project

Abstract: Background:The NHS Bowel Cancer Screening Programme (BCSP) in England does not involve general practitioners (GPs). Uptake is ∼58%. The Practice Endorsed Additional Reminder Letter (PEARL) study piloted a GP-endorsed reminder letter.Methods:General practices in Wessex with uptake <55% (prevalent invitations) were invited to participate. Subjects who had been invited for screening, sent a standard 28-day BCSP reminder letter but had not returned a test kit within 30 days of the standard reminder were sent a sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 19 publications
2
31
0
Order By: Relevance
“…Another would see general practitioners performing the risk assessment, creating the opportunity to discuss and then manage modifiable risk factors. The latter approach may also result in greater uptake of the risk assessment and resulting screening recommendations, as demonstrated by studies involving general practitioner endorsement of iFOBT ( 51 , 52 ). Potential barriers to this option include upskilling the current workforce and integration into current general practitioner workflows ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another would see general practitioners performing the risk assessment, creating the opportunity to discuss and then manage modifiable risk factors. The latter approach may also result in greater uptake of the risk assessment and resulting screening recommendations, as demonstrated by studies involving general practitioner endorsement of iFOBT ( 51 , 52 ). Potential barriers to this option include upskilling the current workforce and integration into current general practitioner workflows ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…GP surgeries are advised to add a personal message to letters on the grounds that GP endorsement encourages patients to accept the invitation of screening. [21,22] Even though a caveat is added that the decision to accept cervical screening is 'your choice', this is at odds with the pragmatic implication of the rest of the message.…”
Section: Patient Choicementioning
confidence: 99%
“…The PEARL study also highlight role of the GP for cancer screening and demonstrated that people encouraged by a GP were more likely to respond to a screening invitation. Moreover, patients who ignored reminder letters from prevention centres might still have reacted to an endorsed reminder from their GP [27].…”
Section: Role Of the Gp In Screening For Gastrointestinal Cancermentioning
confidence: 99%